Job Insecurity and Abusive Supervision - Mao, Hsiao-Yen; Chien, Yuan-Yu; Hsieh, An-Tien (Relations industrielles / Industrial Relations, 2019)
Because of increased market uncertainty, employers today often do not guarantee job security and employees increasingly perceive such a state, often with trepidation. Employees who have relatively insecure jobs tend to feel mistreated by their managers. This study examines the relationship between the work places where jobs are mostly insecure and employee perception of abusive supervision, and the moderating role of a relational mechanism of perceived social worth at work.The conservation of resources (COR) perspective is used to guide analysis. This perspective provides competing rationales for employee acquisition/preservation of resources and ensuing abusive supervision. In a two-wave panel survey, 271 full-time employees with various occupations completed two questionnaires. Results indicate that job insecurity is positively associated with abusive supervision. This association is stronger for employees who perceive higher social worth at work.There is limited research investigating how managerial/leadership effectiveness varies in workplaces where job’s are insecure. Moreover, a relational mechanism of social worth has rarely been used to examine the phenomenon of job insecurity. Although literature shows employees’ perception of job insecurity leads them to increase work input/effort to make themselves more valuable and worthy of remaining in the organization, this does not mean that they will be more likely to notions such as management prerogative on their employer’s authority. Ironically, leadership, in particular, tends to be undermined when jobs are insecure as our findings show that insecure subordinates tend to perceive themselves experiencing supervisory abuse. To address this malaise, practical implications for organizations, supervisors, and subordinates are proposed and complementary practices are discussed to differentiate high social-worth employees from others.